2013
DOI: 10.1039/c3fd00040k
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric aerosol as a reactive intermediate

Abstract: In tropospheric chemistry, secondary organic aerosol (SOA) is deemed an end product.Here, on the basis of new evidence, we make the case that SOA is a key reactive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 96 publications
(180 reference statements)
3
54
0
Order By: Relevance
“…In this experiment the initial NO 2 concentration (NO 2 (i) = 47 ppb) was higher than the measured outdoor levels. However, as discussed in previously published papers, NO 2 may react with O 3 and OH − (formed at ambient relative humidity) in the reaction chamber, leading to the formation of HNO 3 − , HONO, and other possible derivatives, and hence to a reduction in the NO 2 levels and the spore reaction rates (Colussi et al, 2013;Crutzen, 1988;Finlayson-Pitts and Pitts, 2000;Song et al, 2011;Spicer et al, 1993).…”
Section: Resultsmentioning
confidence: 95%
“…In this experiment the initial NO 2 concentration (NO 2 (i) = 47 ppb) was higher than the measured outdoor levels. However, as discussed in previously published papers, NO 2 may react with O 3 and OH − (formed at ambient relative humidity) in the reaction chamber, leading to the formation of HNO 3 − , HONO, and other possible derivatives, and hence to a reduction in the NO 2 levels and the spore reaction rates (Colussi et al, 2013;Crutzen, 1988;Finlayson-Pitts and Pitts, 2000;Song et al, 2011;Spicer et al, 1993).…”
Section: Resultsmentioning
confidence: 95%
“…14−17 Aerosol uptake of NO 2 with γ on the order of 10 −4 ∼ 10 −3 has been observed and linked to the catalysis effect of photochemically formed dicarboxylic acid anions. 17 These findings suggest that tropospheric aerosols might play a much more important role in daytime HONO production than previously thought over regions with high loads of aerosols that have favorable chemical compositions.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Liu et al (2012b) investigated satellite products and reported a relatively high concentration of glyoxal (discarboxylic acid precursor) in central China. Colussi et al (2013) reported that the carboxylate anions can work as a catalyst to promote the disproportionation of NO 2 on water and HONO formation. This may have driven the heterogeneous HONO generation in the northern central plain of China.…”
Section: Effect On O 3 Spatial Distributionmentioning
confidence: 99%
“…However, the importance of aerosol surface area with respect to heterogeneous HONO formation remains controversial. Some studies reported relatively low (10 −7 to 10 −6 ) NO 2 uptake coefficients on the aerosol surface area (Stemmler et al 2007), whereas others observed uptake coefficients of 10 −4 to 10 −3 (Colussi et al 2013).…”
Section: Introductionmentioning
confidence: 99%